Computational Model for the Evaluation of Reinforced Concrete Silos Subjected to Thermal Load - Khalifa, W. M. A.; El-Kashif, K. F. O. (Engineering, Technology & Applied Science Research, 2019)
Silos are special structures subjected to many different unconventional loading conditions like temperature differences which result in unusual failure modes. So, it is necessary for many codes to maintain and study the effect of thermal loads in design. The evaluation of design and construction practices is an essential step in the development of the design code for reinforced concrete (RC) silos, especially in arid zones like Saudi Arabia. This work evaluates the effect of thermal loads on silo wall design in terms of applied forces and stresses. These thermal loads affect the silo walls in two main manners, tangential oriented stresses (circumferential stress) due to thermally induced surcharge pressure during cooling of a filled silo structure and stresses due to differences of temperature across the wall thickness. A computation analytical finite element model (FEM) has been applied in a commercial analyzing program (SAP 2000 version 16). Various code provisions were used with comparison with the FEM results. For hoop forces, EU regulation, German standard, and Polish norm provisions were compared with a linear FEM with two parameters, wall thickness and temperature difference. For oriented stresses in silo wall, the American concrete institute (ACI) provisions were used in comparison with linear and nonlinear FEM with the same two parameters, wall thickness and temperature difference. This work showed that the nonlinear analysis of FEM has good matching with the corresponding values in ACI, leading to the conclusion that nonlinear analysis is more accurate than linear analysis. Moreover, the study results of hoop forces showed a distinct pattern with the temperature difference, silo radii, and insignificant silo wall thickness for each of FEM, EU, and Poland codes. This study is used for the rapid determination of critical areas of concern for critical loading combinations and for varying silo configurations.